Buddhist and Islamic orders in southern Asia: comparative perspectives - Feener, R. Michael; Blackburn, Anne M. (University of Hawaiʻi Press, 2019)
Sufis and saṅgha in motion : toward a comparative study of religious orders and networks in southern Asia / Anne M. Blackburn and R. Michael Feener -- ʻAbdallāh b. ʻUmar ibn Yaḥyā and the Ṭarīqa ʻAlawiyya in the early-nineteenth-century Indonesian archipelago / Ismail Fajrie Alatas -- The itineraries of "Sīhaḷa Monk" Sāralaṅkā : Buddhist interactions in eighteenth-century southern Asia / Alexey Kirichenko -- Challenging orders: Ṭarīqas and Muslim society in southeastern India and Laṅkā, ca. 1400-1950 / Torsten Tschacher -- Whose orders? : Chinese popular god temple networks and the rise of Chinese Mahāyāna Buddhist monasteries in Southeast Asia / Kenneth Dean -- Sufi "orders" in Southeast Asia : from private devotions to social network and corporate action / Martin van Bruinessen -- Shaṭṭāriyya Sufi scents : the literary world of the Surakarta Palace in nineteenth-century Java / Nancy K. Florida -- Negotiating order in the land of the dragon and the hidden valley of rice : local motives and regional networks in the transmission of new "Tibetan" Buddhist lineages in Bhutan and Sikkim / Amy Holmes-Tagchungdarpa